أثر جائحة كورونا على الرقابة الجبائية في المؤسسات - بومهدي, فتيحة (My University, 2022)
Most institutions always strive to adapt to the changes taking place in their surrounding environment in which they operate It is exposed to risks and crises that reflect on its performance in general and its financial performance in particular, and with The emergence of the Corona pandemic, which struck all the world, which had effects on various health aspects, and various In the economic fields, we tried, through our theoretical and applied study, to answer the problem of knowing the role of fiscal control on the public institution and the extent of the impact of the Corona pandemic on its financial performance. We chose the Neighborhood Tax Authority in the state of Mostaganem Sidi Ali by studying the most important and most appropriate indicators for measuring financial performance during that period during which the pandemic spread and the period before it and the comparison between them, where we can say the period of the Corona pandemic in general and what it left behind. What measures have been taken to reduce it?
دراسة حالة الإصلاح الضريبي بالمركز الجواري للضرائب سيدي على مستغانم
Keywords: fiscal control - the neighborhood institution for taxes - financial performance - the corona pandemic - performance indicators.